2008
DOI: 10.4137/cmc.s355
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fetal Autonomic Nervous System Activity by Fetal Magnetocardiography

Abstract: Aim: To clarify the signifi cance of heart rate variability for the evaluation of an autonomic nervous system (ANS) in the normal fetus using fetal magnetocardiography (FMCG).Methods: Subjects consisted of normal pregnancy (n = 35) at 28-39 weeks gestation. FMCG was recorded using 64-channel magnetocardiography (MCG) in a magnetically shielded room. The QRS interval was derived from signal-averaged MCG. The R-R interval variability induced by an R-wave trigger was eventually adopted to calculate for time-domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…21) Because fetal evoked MEGs may be difficult to perform as a general clinical application, we reviewed the significance of fetal heart rate variability for evaluating fetal ANS activity. Using a 64-ch MCG, Fukushima, et al found that the activity of the sympathetic and parasympathetic nervous systems, as evaluated from the LF/HF ratio, were enhanced at gestational ages of 32 weeks and later, 13) consistent with previous reports of a conversion point at 32 weeks of gestation. 22,23) We found that the ANS activity, as evaluated by the CV and LF/ HF ratio using SAVP-ECG, was remarkably enhanced just after birth.…”
Section: )supporting
confidence: 70%
“…21) Because fetal evoked MEGs may be difficult to perform as a general clinical application, we reviewed the significance of fetal heart rate variability for evaluating fetal ANS activity. Using a 64-ch MCG, Fukushima, et al found that the activity of the sympathetic and parasympathetic nervous systems, as evaluated from the LF/HF ratio, were enhanced at gestational ages of 32 weeks and later, 13) consistent with previous reports of a conversion point at 32 weeks of gestation. 22,23) We found that the ANS activity, as evaluated by the CV and LF/ HF ratio using SAVP-ECG, was remarkably enhanced just after birth.…”
Section: )supporting
confidence: 70%
“…11). Inter-group changes in LF/HF in the normal group increased significantly with gestation period (one-way ANOVA: P = 0.003) [7,8] (Fig. 12).…”
Section: Sustained Vt -Sinus Rhythm Sinus Rhythmmentioning
confidence: 88%
“…CV RR over the gestational age periods in normal pregnancy showed no statistical differences on one-way ANOVA [7,8] ( Fig. 10).…”
Section: Sustained Vt -Sinus Rhythm Sinus Rhythmmentioning
confidence: 94%
See 1 more Smart Citation
“…It is known that the fetal autonomic nervous system and cardiac function develop as gestation progresses [56], and these functions are reflected in the correlation of fetal heart rate fluctuations with gestational age [7]. Therefore, it is important to study how fetal cardiac function responds to postural changes, as gestational age increases.…”
Section: Introductionmentioning
confidence: 99%